Time of Contempt (The Witcher #4) - Andrzej Sapkowski (London Gollancz, 2013)
Geralt is a witcher: guardian of the innocent; protector of those in need; a defender, in dark times, against some of the most frightening creatures of myth and legend. His task, now, is to protect Ciri. A child of prophecy, she will have the power to change the world for good or for ill -- but only if she lives to use it. A coup threatens the Wizard's Guild. War breaks out across the lands. A serious injury leaves Geralt fighting for his life... ... and Ciri, in whose hands the world's fate rests, has vanished... The Witcher returns in this sequel to Blood of Elves.
Keywords: Fantasy; Fiction; Adventure; Adult